2009
DOI: 10.1021/ja9042356
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Nanocontainers Made Porous Using a Bacterial Toxin

Abstract: Encapsulation of a biological molecule or a molecular complex in a vesicle provides a means of biofriendly immobilization for single molecule studies and further enables new types of analysis if the vesicles are permeable. We previously reported on using DMPC (dimyristoylphosphatidylcholine) vesicles for realizing porous bioreactors. Here, we describe a different strategy for making porous vesicles using a bacterial pore-forming toxin, α-hemolysin. Using RNA folding as a test case, we demonstrate that protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 38 publications
(87 reference statements)
1
67
0
Order By: Relevance
“…On a related note, it was shown that hGQ can be encapsulated within lipid vesicles, typically dimyristoylphosphatidylcholine (DMPC), that are immobilized on a supported lipid bilayer (such as EggPC), PEG, or BSA surface (Ishitsuka et al ; Okumus et al 2004; Cisse et al 2007; Okumus et al 2009; Okumus and Ha 2010). Comparative studies of hGQ that is encapsulated within a vesicle or immobilized on a BSA surface yielded consistent results in terms of the observed FRET levels (Lee et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…On a related note, it was shown that hGQ can be encapsulated within lipid vesicles, typically dimyristoylphosphatidylcholine (DMPC), that are immobilized on a supported lipid bilayer (such as EggPC), PEG, or BSA surface (Ishitsuka et al ; Okumus et al 2004; Cisse et al 2007; Okumus et al 2009; Okumus and Ha 2010). Comparative studies of hGQ that is encapsulated within a vesicle or immobilized on a BSA surface yielded consistent results in terms of the observed FRET levels (Lee et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Following a similar reasoning, researchers have been able to capture fluorescently labeled binding partners in small (100-200 nm), surface-tethered lipid nanovesicles and study their interactions through single-molecule FRET measurements (Figure 2b) [51][52][53]54 ]. The volume of a 100-nm vesicle is two orders of magnitude smaller than that of a diffraction-limited volume and thus allows proteins to be visualized at the single-molecule level at much higher effective concentrations than hitherto possible.…”
Section: The Concentration Problemmentioning
confidence: 98%
“…Furthermore, lipid vesicles or trapped droplets do not generally allow exchange of buffer within the confined volume, which is problematic for studying enzymes, since the reactants may quickly become consumed. Although nanovesicles can be adapted to allow exchange of small molecules through nanopores with the buffer in which the vesicles are immersed, this is not useful in the case that small molecule reactants, such as ATP, are the fluorescent substrates to be imaged [7]. Another alternative strategy for increasing the concentration limit that avoids three-dimensional confinement, PhotoActivation, Diffusion, and Excitation (PhADE), was recently demonstrated [8].…”
Section: Introductionmentioning
confidence: 99%